Room of their own women's voices in Africa - Suri Twinkle (New Delhi Books Plus, 2006)
This book is the pioneering efforts of accomplished African women writers in a visible and effective voice of protest against colonial and post colonial servitude as they make a tremendous effort to resurrect, explicate and canonize the literary heritage
Keywords: Africa; Africa; African fiction (English); Feminism; Feminism and literature; Feminist fiction; Literature; Women writers